FINITE ELEMENT ANALYSIS WITH STATIC AND DYNAMIC CONDITIONS OF SPARE WHEEL CARRIER FOR OH 1526 FABRICATED BY SAPH 440 HOT ROLLED STEEL - Norbertus Krisna Aditya Utomo; Lydia Anggraini (President University, 2019)
Spare Wheel Carrier is a component that must exists in a heavy duty vehicle. The function of this part is to store additional wheel in order to deal with punctures that might happen to the tire. This part is usually placed in the middle of the vehicle in order to maintain the position of center of gravity of the vehicle. The purpose of this research is to analyze the strength of SAPH 440 as the manufacturing material of the Spare Wheel Carrier from one automotive company. The Spare Wheel Carrier will endure a load of a replacement tire for its entire cyclic load. The load itself will generate stresses and strains in the part, especially in the welding joint. Therefore, the analysis is to be done to provide the automotive company with the result to determine improvement that should be made. The method that is used in this research is using CATIA software to create the three dimensional model of the part. Later, we import the model to ANSYS software to analyze the equivalent stress, equivalent elastic strain, directional deformation, and cyclic load for steady load, live load, and shock load. The calculation shows that the part can endure the force from steady load, with the estimated cyclic load of 70,723 cycles. But for live load, the stress and strain will be happening around the yield strength and offset yield strength and the estimated cyclic load declining significantly to 6,358.6 cycles. Furthermore, the shock load result stated that the stress and the strain are exceeding the yield strength and reduces the estimated cyclic load to 1,843.9 cycles. In conclusion, the material is proven to be safe for usage as the Spare Wheel Carrier manufacturing material.Keywords. spare wheel carrier, SAPH 440, stress, strain, deformation, cyclic load